HUMAN RESOURCE MANAGEMENT IN THE DEVELOPMENT OF ARABIC LANGUAGE LEARNING AT MADRASAH ALIYAH NEGERI 1 LANGKAT - Muhammad Ikhza Elsya; Muhammad Fadhli; Fatkhur Rohman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze and describe the implementation of human resource management (HRM) for Arabic language teachers in supporting learning development at State Islamic Senior High School (MAN) 1 Langkat, focusing on planning, competency development, performance evaluation, and its contribution to learning quality. This study employed a qualitative approach with a descriptive-exploratory case study design. Data were collected through in-depth interviews with the principal, deputy principal for curriculum, and Arabic language teachers, participatory observations of learning activities and academic supervision, and documentation. Data were analyzed using the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing and verification. Data trustworthiness was ensured through credibility, transferability, dependability, and confirmability criteria. The findings indicate that HRM for Arabic language teachers was implemented systematically through teacher needs identification, competency mapping, teaching assignment, and continuous competency development planning. Competency development was supported through Subject Teacher Conferences (MGMP), workshops, Independent Curriculum training, and academic supervision, followed by regular performance evaluation. These practices contributed to strengthening teacher professionalism, improving teaching performance, fostering more communicative and innovative Arabic language learning, and increasing student participation and learning outcomes. The study concludes that strategic HRM plays an important role in improving the quality of Arabic language learning by strengthening teacher competency.